Implementation of Solution-Focused Brief Counseling to Increase the Resilience of Victims of Sexual Harassment - Apriana Putri, Ria; Kusnadi, Kusnadi; Fitri, Hartika Utami (Grief and Trauma, 2023)
This study entitled the application of Individual Counseling with a Solution-Focused Brief Counseling Approach to Increase the Resilience of Victims of Sexual Harassment (Case Study of Client "S" at Sentra Budi Perkasa Palembang). This study aims to increase the client’s "S" resilience using individual counseling with the SFBC approach. The research was conducted using a qualitative approach with the case study method. The subjects used in this study were clients "S" and Social Workers at Sentra Budi Perkasa Palembang. The research tools used were observation, interviews, and documentation. Then this study conducted data analysis in three stages: pattern matchmaking, explanation, and time series analysis. The study results are that client "S" is a young victim of sexual harassment whose resilience is quite good but needs to be further improved so that mental and physical disturbances do not occur in the future. Therefore, the researcher used this approach of solution-focused brief counseling so that the client "S" can become fully resilient in facing the challenges and obstacles ahead.